2022
DOI: 10.33860/jik.v15i4.659
|View full text |Cite
|
Sign up to set email alerts
|

Riwayat Pengobatan dan Komorbid Diabetes Mellitus Berhubungan Dengan Kejadian Tuberkulosis Resisten Obat

Abstract: Tujuan penelitian untuk menganalisis hubungan antara riwayat pengobatan Tuberkulosis (TB) sebelumnya dan komorbid Diabetes Mellitus (DM) dengan kejadian Tuberkulosis Resisten Obat (TB RO) di Kabupaten Poso. Metode penelitian yaitu observasional analitik dengan desain studi case control. Populasi yaitu seluruh pasien penderita TB di Kabupaten Poso. Sampel yaitu 32 pasien TB RO sebagai kelompok kasus dan 32 penderita TB Sensitifi Obat (TB SO) sebagai kelompok kontrol. Pengambilan data dengan mengidentifikasi dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
5
2
0
Order By: Relevance
“…If the air containing TB bacteria is inhaled, there is a chance that those nearby will contract tuberculosis; if the immune system is compromised, transmission will be facilitated. In addition, this study is consistent with research conducted by Manggasa 2022 (12) regarding the History of Treatment and Comorbid Diabetes Mellitus Associated with the Incidence of Drug-Resistant Tuberculosis, which states that TB disease can be contracted even if there is no history of prior treatment.…”
Section: Medical History and Tb Treatment Status Correlationsupporting
confidence: 91%
See 4 more Smart Citations
“…If the air containing TB bacteria is inhaled, there is a chance that those nearby will contract tuberculosis; if the immune system is compromised, transmission will be facilitated. In addition, this study is consistent with research conducted by Manggasa 2022 (12) regarding the History of Treatment and Comorbid Diabetes Mellitus Associated with the Incidence of Drug-Resistant Tuberculosis, which states that TB disease can be contracted even if there is no history of prior treatment.…”
Section: Medical History and Tb Treatment Status Correlationsupporting
confidence: 91%
“…This research is consistent with the findings of manggasa 2020 (12) and Lilia Damayanti 2022 (2), who discovered that the majority of TB patients who did not have a history of drug failure were new TB patients. This contradicts the results of a study conducted by Nurmala 2020 (15) in Kupang, which found that more TB patients had failed treatment.…”
Section: Risk Characteristics Of Previous Tb Treatmentsupporting
confidence: 91%
See 3 more Smart Citations